Does nutrition play a role in the prevention and management of sarcopenia?. Issue 4 (August 2018) - ,; Al-Daghri, N.; Allepaerts, S.; Bauer, J.; Brandi, M.L.; Cederholm, T.; Cherubini, A.; Cruz Jentoft, A.; Laviano, A.; Maggi, S.; McCloskey, E.V.; Petermans, J.; et al.
Summary: There is a growing body of evidence that links nutrition to muscle mass, strength and function in older adults, suggesting that it has an important role to play both in the prevention and management of sarcopenia. This review summarises the discussions of a working group [ESCEO working group meeting 8th September 2016] that met to review current evidence and to consider its implications for preventive and treatment strategies. The review points to the importance of 'healthier' dietary patterns that are adequate in quality in older age, to ensure sufficient intakes of protein, vitamin D, antioxidant nutrients and long-chain polyunsaturated fatty acids. In particular, there is substantial evidence to support the roles of dietary protein and physical activity as key anabolic stimuli for muscle protein synthesis. However, much of the evidence is observational and from high-income countries. Further high-quality trials, particularly from more diverse populations, are needed to enable an understanding of dose and duration effects of individual nutrients on function, to elucidate mechanistic links, and to define optimal profiles and patterns of nutrient intake for older adults.